DAMPAK HARGA BERAS TERHADAP KONSUMSI BERAS RUMAHTANGGA PETANI KELAPA SAWIT DI DESA INDRA SAKTI KECAMATAN TAPUNG KABUPATEN KAMPAR - Elinur '; Asrol ' (Indonesian Journal of Agricultural Economics, 2015)
Rice is dominant food commodity by Indonesian society. Instability price rice influence consumption of rice in people, as well as for household palm oil farmers. This research analyzed response rice consumption on dominant factor effecting, and impact rice price on rice consumption household palm oil farmers. This research used survey method. Sampling method used simple random sampling and amount of sample are 35 household palm oil farmers. Method of data analysis used econometric with estimasi method Oldinary Least Square (OLS). There are result in the research, firt; response of rice price and the number of family members to shift rice consumption household is elastic. It’s means changes in the price of rice and the number of family members take large effect to consumption household palm oil farmers. Response of income and education of farmer’s wife to shift rice consumption household is inelastic. Second; increasing of rice price and income of household farmers in the same proportion impact negative to rice consumption household palm oil farmers. Increasing income can’t eliminate negative impact to increasing of rice price. It’s mean stabilization policy of rice price batter than increasing income policy household palm oil farmers.